Expression and Hydroxylamine Cleavage of Thymosin Alpha 1 Concatemer - Gong, Xing-Guo; Lu, Min-Kan; Lai, Zong-Teng; Zhou, Liang; Xie, Yi (BioMed research international, 2008)
Human thymosin alpha 1 (Tα1) is an important peptide in the development and senescence of immunological competence in human, and many studies have reported the expression of this peptide. In this study, we designed and synthesized the Tα1 gene according to the E. coli codon usage preference and constructed a 6×Tα1 concatemer. The latter was inserted into an E. coli expression vector pET-22b (+), and transformed into E. coli BL21 (DE3). After induction with IPTG, the concatemer protein was successfully expressed in E. coli then cleaved by hydroxylamine to release the Tα1 monomer. Gly-SDS-PAGE and mass spectrometry confirmed that the recombinant protein was cleaved as intended. The bioactivity of the Tα1 monomer was analyzed by lymphocyte proliferation and by mitochondrial activity in two different tumor cell lines. This study provides a description of the preparation of a bioactive Tα1, which may prove useful in future biomedical research.